2018
DOI: 10.1186/s12907-018-0076-1
|View full text |Cite
|
Sign up to set email alerts
|

Biphasic low-grade nasopharyngeal papillary adenocarcinoma: a case report and literature review

Abstract: BackgroundLow-grade nasopharyngeal papillary adenocarcinoma (LGNPPA) is distinctly rare. We report a patient with a uniquely biphasic LGNPPA; additionally, we review similar tumors reported in the literature.Case presentationA 56-year-old man presented with an asymptomatic pedunculated tumor in the vault of the nasopharynx, at the junction of the nasal septum and the roof, which was discovered during screening for laryngeal cancer. To obtain a definitive diagnosis, the patient underwent endoscopic endonasal su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 20 publications
1
8
0
Order By: Relevance
“…Recently, Petersson et al [2] reported the presence of a spindle cell component in a patient with TLLG-NPPA. Only six cases of TLLG-NPPA exhibiting spindle cells have been reported to date [2,3,[8][9][10]. Here, we present another case of biphasic TLLG-NPPA that contained a prominent spindle cell component in a 50-year-old woman.…”
Section: Introductionmentioning
confidence: 81%
See 2 more Smart Citations
“…Recently, Petersson et al [2] reported the presence of a spindle cell component in a patient with TLLG-NPPA. Only six cases of TLLG-NPPA exhibiting spindle cells have been reported to date [2,3,[8][9][10]. Here, we present another case of biphasic TLLG-NPPA that contained a prominent spindle cell component in a 50-year-old woman.…”
Section: Introductionmentioning
confidence: 81%
“…Only five case reports describing six patients with TLLG-NPPA exhibiting spindle cells have been published to date (Table 2) [2,3,5,[8][9][10]. The spindle cell component was prominent in only two of those cases [2,8]. Histologically, the spindle cell component did not exhibit severe nuclear pleomorphism or atypical mitoses.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…The spindle cell component was found in our case. In the previous literature up to 2019, only five cases of TL-LGNPPA with a prominent spindle cell component, named "biphasic low-grade nasopharyngeal papillary adenocarcinoma, " had been reported (7,10,12,26). Whether the etiology of biphasic LGNPPA differs from TL-LGNPPA without the spindle cell component and the reason why it develops in TL-LGNPPA remain unknown.…”
Section: Discussionmentioning
confidence: 99%
“…In their report, biphasic LGNPPA was differentiated from these tumors based on diffuse positivity of CK and no evidence of gene alternations such as SYT-SSX1/2 fusion transcripts t(X; 18) (p11.2; q11.2) against a biphasic synovial sarcoma, the absence of immunopositivity for CEA, calcitonin, and chromogranin A against medullary thyroid carcinoma, and the difference in originating regions or the expression of TTF-1 against a group of enigmatic neoplasms, respectively (12). Only one report mentioned TL-LGNPPA with squamous differentiation (22); however, Yokoi et al posited that the development of spindle cells occurred independently of squamous differentiation as the tumors were negative for CK5/6 and p40 (26). Further research and accumulation of cases are needed to elucidate the pathogenesis of TL-LGNPPA with the spindle cell component.…”
Section: Discussionmentioning
confidence: 99%